Research on HPLC Experimental Platform Component Scheme. Issue 1 (1st April 2022) - Liang, Yutu; Li, Bo; Li, Xingnan; Deng, Xiaozhi; Lu, Jiangang; Shi, Zhan
Abstract: Power line communication is a kind of communication mode which uses power line as transmission medium and carries on data transmission and information exchange through carrier. Power line has wide distribution, high economy, high transmission rate and good reliability. However, as a communication mode without special transmission media, there is still a lack of power line communication experimental platform in the industrial field. The communication experiment platform is composed of power line carrier field test platform, protocol consistency test platform, interconnection test platform and courts simulation platform. In this paper, the design scheme of the experimental platform is proposed from the aspects of hardware and software respectively. In terms of technology, the requirements of reliability, efficiency, enforceability and practicability are fully considered.